Raman and fluorescence micro-spectroscopy applied for the monitoring of sunitinib-loaded porous silicon nanocontainers in cardiac cells - Tolstik, E.; Gongalsky, M. B.; Dierks, J.; Brand, T.; Pernecker, M.; Pervushin, N. V.; Maksutova, D. E.; Gonchar, K. A.; Samsonova, J. V.; Kopeina, G.; Sivakov, V.; Osminkina, L. A.; et al. (Frontiers in Pharmacology, 2022)
Nanomaterials are a central pillar in modern medicine. They are thought to optimize drug delivery, to enhance the therapeutic efficacy and to reduce side-effects. To foster this technology, analytical methods are of need that validate the localization and distribution of these nanomaterials but also their compatibility with cells, drugs and drug release. In the present work, we assessed nanoparticles based on porous silicon (pSiNPs) loaded with the clinically used tyrosine kinase inhibitor sunitinib for their effectiveness of drug delivery, release and their toxicity in colon cancer cells (HCT 116 cells) and cardiac myoblast cells (H9c2) using Raman micro-spectroscopy, high-resolution fluorescence microcopy, along with biological methods for toxicological effects. We produced pSiNPs with a size of about 100 nm by grinding of mesoporous silicon films. pSiNPs allowed an effective loading of sunitinib due to their high porosity. Photoluminescence properties of the nanoparticles within the visible spectrum allowed the visualization of their uptake in cardiac cells. Raman micro-spectroscopy not only allowed the detection of the uptake and distribution of pSiNPs within the cells via a characteristic silicon Raman band at about 518-520 cm-1, but also the localization of the drug based on its characteristic molecular fingerprints. The cytotoxicity studies by Western blot analyses of apoptotic marker proteins such as caspase-3, and the detection of apoptosis by subG1 positive cell fractions in HCT 116 and MTT analyses in H9c2 cells, suggest a sustained release of sunitinib from pSiNPs and delayed cytotoxicity of sunitinib in HCT 116 cells. The analyses in cardiac cells revealed that pSiNPs are well-tolerated and that they may even protect from toxic effects in these cells to some extent. Analyses of the integrity of mitochondrial networks as an early indicator for apoptotic cellular effects, seem to validate these observations. Our study suggests pSiNPs-based nanocontainers for efficient and safe drug delivery, and Raman-microspectroscopy as reliable method for their detection and monitoring. Thus, the herein presented nanocontainers and analytical methods have the potential to allow an efficient advancement of nanoparticles for targeted and sustained intracellular drug release that is of need e.g. in chronic diseases and for the prevention of cardiac toxicity.